Active media : Investigation of the process of mixing reagents in the laser chamber of active medium generators of continuous-wave chemical lasers with promising nozzle arrays. (31st October 2020) - Avdeev, A V; Katorgin, B I
Abstract: It is shown that the use of a toothed nozzle array in the active medium generator (AMG) of continuous-wave chemical lasers (CWCLs) allows more efficient mixing of reagents to be achieved in the laser chamber than in an AMG with a slit nozzle array. The results of calculations of parameters of the active medium of a DF CWCL operating in the gain regime for the AMG with traditional and promising nozzle array designs are presented. A kinetic model of processes in the DF CWCL active medium is proposed, which allows obtaining a good agreement with the results of measurements of the small-signal gain.